Collaborating on ESG consulting, reporting, and communicating education: Using partner maps for capability building design - Liao, Han-Teng; Pan, Chung-Lien; Zhang, Yuan (Frontiers in Environmental Science, 2023)
Given the rising demand for environmental, social, and governance (ESG) talents, this study aims to provide a multidisciplinary outlook of specific capability requirements for ESG talents, focusing on the use of ESG and carbon information, thereby providing a roadmap for ESG education. Following design science framework conventions and running design workshops that integrate design thinking of “how might we” design questions, literature analysis, and expert interviews across disciplines, this study presents findings regarding three main activities—consulting, reporting, and communicating. Based on the iterations of design workshops that adopt a circular economy-based partner map design canvas for stakeholder analysis with procedures such as expert interviews and literature analysis, three partner/capability maps were generated to map stakeholders and explore the capabilities needed. ESG and carbon information digital and data skills emerged as the core capability to complete all the three tasks. A conceptual framework—a Smart System of ESG and Carbon Information—is proposed to summarize planning, operating, and communicating with ESG and carbon information, along with high-level organizational actions and talent capabilities. It identifies the building blocks of an ESG operating system within an enterprise to engage various stakeholders for value-creation collaboration. Despite the limitation of a lack of comprehensive review and limited geographic and disciplinary representation, this study provides a roadmap for enterprises and universities to explore and define talent requirements and create specific education and training programs.